Classification of west german business cycles - Ullrich Heilemann; Heinz Josef Münch (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
This paper applies linear discriminant analysis to classify West German business cycles from 1955 to 1994 into a four phase scheme (upswing, downswing, and upper/lower turning point phases). It describes the scheme as well as the selection of the classifying variables, and presents classification results for various sample periods. Special attention is given to changes of the explanatory power of the variables and its implication for changes of West German cycle patterns.
Keywords: E32; E29; 519